2016
DOI: 10.4155/fmc-2016-0117
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Histone Deacetylase 8 as a Therapeutic Approach to Cancer and Neurodegenerative Diseases

Abstract: Histone deacetylase 8 (HDAC8), a unique class I zinc-dependent HDAC, is an emerging target in cancer and other diseases. Its substrate repertoire extends beyond histones to many nonhistone proteins. Besides being a deacetylase, HDAC8 also mediates signaling via scaffolding functions. Aberrant expression or deregulated interactions with transcription factors are critical in HDAC8-dependent cancers. Many potent HDAC8-selective inhibitors with cellular activity and anticancer effects have been reported. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 121 publications
0
64
0
Order By: Relevance
“…Moreover, HDAC8 has been implicated in inactivation of the tumor suppressor p53 in acute myeloid leukemia stem cells (Qi et al, 2015). These observations have led to the proposal that HDAC8 is a potential target for cancer treatment (Chakrabarti et al, 2016). Indeed, a number of HDAC8-specific inhibitors are in early development for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HDAC8 has been implicated in inactivation of the tumor suppressor p53 in acute myeloid leukemia stem cells (Qi et al, 2015). These observations have led to the proposal that HDAC8 is a potential target for cancer treatment (Chakrabarti et al, 2016). Indeed, a number of HDAC8-specific inhibitors are in early development for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The 4-methoxybenzyl ts into the subpocket of HDAC8 which may be a reason for the selectivity toward HDAC8 enzyme. 90 Zhang et al reported a series of tetrahydroisoquinolinebased hydroxamic acid HDACis. 91 The tertiary butyloxycarbonyl (Boc) group was located on the secondary amine atom and 4-methyloxy-phenyl group seemed benecial to HDAC8 inhibitory activity.…”
Section: Class I Selective Hdacismentioning
confidence: 99%
“…In fact, several HDAC inhibitors have been applied for treatment of T-cell lymphoma, such as SAHA (suberoylanilide hydroxamic acid, Vorinostat) (Negmeldin and Pflum, 2017) and Belinostat (Poole, 2014), and Panobinostat (Garnock-Jones, 2015). Unfortunately, these FDA approved drugs are relatively non-selective and inhibit most of the zincdependent HDAC subtypes (Yang, 2011;Qiao et al, 2013), which could cause several mild or severe toxic effects associated with the treatment, such as dehydration, thrombocytopenia, anorexia, and cardiac arrhythmia (Chakrabarti et al, 2016;Buonvicino et al, 2018;Cosenza and Pozzi, 2018;Laino et al, 2019). In addition, due to the physicochemical properties of hydroxamic acid group as the ZBG, some drawbacks have been exposed, including poor stability, easy metabolism, weak binding ability to class IIa isozymes, and poor selectivity, making the design and discovery of HDAC inhibitors with novel zinc binding group (ZBG) more necessary (Di Micco et al, 2008;Botta et al, 2011;Burli et al, 2013;Zhao et al, 2018;Banerjee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%